Pheromone-based monitoring and population dynamics of Spodoptera frungiperda: implications for maize IPM in Lampung Province, Indonesia - Puji Lestari; Mega Kartika Hermawan; Nur Rakhman Syaiful Akhdar; Fatnuri Fatnuri; Lestari Wibowo; Selvi Helina; Yuyun Fitriana; I Gede Swibawa; Radix Suharjo; Purnomo Purnomo; Solikhin Solikhin; Hamim Sudarsono; F.X. Susilo; Agus M. Hariri; Made Wiradika (Universitas Lampung, 2026)
Spodoptera frugiperda is a major pest of maize, capable of causing damage throughout all crop growth stages. This study evaluated the use of sex pheromone traps to monitor adult male populations of S. frugiperda, characterize population dynamics during maize growth, and determine optimal trap density under field conditions. A trap density experiment was conducted using four pheromone trap densities (10, 20, 30, and 40 trap/ha⁻¹), each replicated five times. Adult moth captures were recorded at 7-day intervals from trap installation until harvest. In a separate assessment, the intensity of leaf and ear damage was compared between maize plots equipped with pheromone traps and conventional plots without pheromone deployment. Adult capture data revealed clear population fluctuations, with peak abundance occurring during the early vegetative stage of maize, followed by a gradual decline toward harvest. Increasing trap density significantly increased the number of male moths captured, indicating a density-dependent response to pheromone deployment. Maize plots with pheromone traps consistently exhibited lower leaf and ear damage than conventional plots, demonstrating a strong association between reduced adult populations and decreased crop injury. These results indicate that pheromone traps are effective tools for monitoring S. frugiperda populations and for identifying critical intervention periods within an integrated pest management (IPM) framework. While primarily serving as monitoring devices, higher trap densities also showed potential to reduce mating success when deployed over sufficiently large areas. The species-specific nature of pheromone traps further supports environmentally sustainable pest management by minimizing non-target effects.